Strength and conditioning for fencing - Turner, A.; Miller, S.; Stewart, P.; Cree, J.; Ingram, R.; Dimitriou, L.; Moody, J.; Kilduff, L. (Strength and Conditioning Journal, 2013)
Scientific research into fencing is sparse and little relates to strength and conditioning. In our experience of working within fencing, it is a predominately anaerobic sport characterised by explosive high-power movements. Consequently, fencers should be cautious of some of the traditional training methods currently used such as long slow distance running because this is likely to be counterproductive to performance. Instead, exercises and conditioning drills that develop repeat lunge ability, strength, and power should be used. The high proportion of lunging also dictates the need for eccentric strength and control and the ability to reduce muscle damage.